Cooperation of Pax2 and Pax5 in midbrain and cerebellum development - Urbánek, Pavel (The National Academy of Sciences of the USA, 1997)
Midbrain and cerebellum development depends on an organizing center that is located at the midbrain–hindbrain junction of the vertebrate embryo. Expression of the two closely related transcription factors Pax2 and Pax5 overlaps spatially and temporally in this region of the developing central nervous system. To study a possible interaction of these transcription factors in midbrain and cerebellum patterning, we have generated Pax5, Krd double mutant mice. The transgene-induced Krd mutation corresponds to an ≈7-centimorgan chromosome 19 deletion that eliminates the entire Pax2 locus. The heterozygous Krd mutation deleting one Pax2 allele had no effect on midbrain and cerebellum development. Moreover, only minor developmental defects were previously observed at the midline of the inferior colliculus and anterior cerebellum in mice that were homozygous for a targeted Pax5 mutation. Similar morphological alterations were observed in 80% of all compound heterozygous Pax5 (+/−) Krd (+/−) mice. However, in the remaining 20% of compound heterozygotes, the inferior colliculi were missing, and the vermis of the cerebellum was severely disrupted due to the failure of the cerebellar primordia to fuse at the midline. Inactivation of the second Pax5 allele in Pax5 (−/−) Krd (+/−) mice resulted in complete loss of the posterior midbrain and cerebellum, as the tissue originating from the midbrain–hindbrain boundary region was deleted in the embryo as early as day 9.5. On the basis of these data, we propose that the cooperation of Pax2 and Pax5 is essential for normal functioning of the organizing center at the midbrain–hindbrain junction.